The role of Piezo1 in immune cells and pregnancy - Fei, Yiming; Liu, Yilin; Zhang, Lijuan (Frontiers in Immunology, 2026)
In innate immunity, Piezo1 influences macrophage polarization, neutrophil migration, inflammation and repair. In adaptive immunity, it modulates T cell mechanosensation, immune synapse formation and B cell antigen presentation. Expressed in endometrium, placental vasculature, placental trophoblast and myometrium, Piezo1 regulates Ca²+ signaling during implantation, NO-dependent placental vasodilation, uterine contractions and inflammation, impacting pregnancy maintenance and labor onset. This review systematically summarizes the pivotal role of the mechanosensitive ion channel Piezo1 in immunoregulation and pregnancy. Firstly, it outlines the molecular structure of Piezo1 alongside its activation and inactivation mechanisms. Secondly, it focuses on Piezo1’s functions within innate and adaptive immune cells (such as macrophages and T cells) and its regulation of immune responses. Subsequently, it delves into Piezo1’s pivotal role across multiple stages of pregnancy, including its influence on uteroplacental vascular remodeling, trophoblast cell fusion, labor initiation, and fetal development. Particular attention is given to its potential bridging function linking immune homeostasis with successful pregnancy. Finally, it outlines the therapeutic potential of targeting Piezo1 in related pregnancy disorders and future research directions. This paper aims to provide insights into the integrated function of mechanobiology within reproductive immunity.